The family in transformation - Nikodem, Krunoslav (Array, 2005)
The fifth chapter is entitled The Family in transformation. The authors discuss marriage, family, children, divorce, family relations and the influence of religiosity on family life. They openly discuss the deep demographic crisis in Croatia, which can be recognised through the indicators of the “ ageing” of the Croatian population and the low rate of reproduction. They see the way out of the demographic erosion in the clearly outlined, permanent family policy.